Model systemu budżetowania w przedsiębiorstwach budowlano-montażowych - Kotapski, Roman (The Model of The Budgeting System in Construction Companies, 2006)
This article describes guidelines for designing the model of budgeting system in construction companies. Some main cost centers and processes in construction companies were shown. Elements of the model of budgeting system in construction companies were also discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 183-193